2020
DOI: 10.3390/agriculture10100455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical and Herbicide Treatments on Weed Densities and Biomass in Two Potato Cultivars

Abstract: The effect of potato cultivar and mechanical or herbicide treatments on weed densities and biomass was determined in a research study on a field, conducted from 2007 to 2009 at the Institute of Plant Breeding and Acclimatization. Included in the study were two cultivars and different weed control treatments, including a mechanical method and metribuzin combined with various herbicides and application timings. Chemical methods of controlling weeds were more effective than mechanical methods to reduce weed densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…They induce quantity and quality losses of the yield and ultimately decrease the net return of the production system with increased production costs. Potato cultivars with a strong, erect shoot growth habit with shorter stems, more branching, and a denser and taller canopy in the early stages of plant growth may be less susceptible to weed interference than cultivars with less lofty plant habit [38][39][40]. Commercial potato growers follow rigorous herbicide application schedules throughout the conventional potato growing season and apply different pesticides.…”
Section: Weed and Pest Management In Potatomentioning
confidence: 99%
See 2 more Smart Citations
“…They induce quantity and quality losses of the yield and ultimately decrease the net return of the production system with increased production costs. Potato cultivars with a strong, erect shoot growth habit with shorter stems, more branching, and a denser and taller canopy in the early stages of plant growth may be less susceptible to weed interference than cultivars with less lofty plant habit [38][39][40]. Commercial potato growers follow rigorous herbicide application schedules throughout the conventional potato growing season and apply different pesticides.…”
Section: Weed and Pest Management In Potatomentioning
confidence: 99%
“…The use of neonicotinoid chemistry as a seed tuber treatment greatly reduced the need to spray insecticide, especially for Colorado potato beetle control, and the amendment with cattle or swine manure led to better crop health and reduced the need for pest and disease treatments [65]. Herbicide selection, herbicide combinations, and application rates and timing determine the effectiveness of the method in weed management [40,[66][67][68]. Barbaś et al [40] found that the chemical method of controlling weeds was the most effective weed control method over a combination of mechanical methods in potato production.…”
Section: Weed and Pest Management In Potatomentioning
confidence: 99%
See 1 more Smart Citation
“…Weeds are a threat to any cultivated crop and negatively impact crop production as they compete with the planted crop for light, nutrients, water, and space and induce quantity and quality losses of the yield and ultimately decrease the net return of the production system with increased production costs. Potato cultivars with a strong, erect shoot growth habit with shorter stems, more branching, and a denser and taller canopy in the early stages of plant growth may be less susceptible to weed interference than cultivars with less lofty plant habit (Pszczółkowski and Sawicka, 2003;Baranowska et al, 2016;Barbaś et al, 2020). Commercial potato growers follow rigorous pesticide application schedules throughout the conventional potato growing season, and apply different pesticides.…”
Section: Weed and Pest Managementmentioning
confidence: 99%
“…The use of neonicotinoid chemistry as a seed tuber treatment greatly reduced the need to spray insecticide, especially for Colorado potato beetle control, and the amendment with cattle or swine manure led to better crop health and reduced the need for pest and disease treatments (VanderZaag, 2010). Herbicide selection, herbicide combinations and application rates and timing determine the effectiveness of the method in weed management (Pawlonka, 2007;Lavlesh Ragha et al, 2018;Zarzecka et al, 2020;Barbaś et al, 2020). Barbaś et al (2020) found that chemical method of controlling weeds was the most effective weed control method over a combination of mechanical methods in potato production.…”
Section: Weed and Pest Managementmentioning
confidence: 99%